2007
DOI: 10.1159/000107678
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Various Dietary Amino Acid Preparations for Phenylketonuric Patients on the Metabolic Profiles along with Postprandial Insulin and Ghrelin Responses

Abstract: Aim: We investigated the metabolic profiles along with insulin and ghrelin responses following ingestion of various amino acid (AA) substitutes commonly used in the treatment of phenylketonuria to study the effects of added macronutrients. Methods: Twenty healthy and 6 phenylketonuric adults ingested AA mixtures with or without carbohydrates and fat (Anamix, Easiphen, or p-am 3; 0.35 g AA/kg body weight); milk powder shakes were used for control purposes. Serum AA, glucose, urea, insulin, and ghrelin were meas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
24
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 18 publications
(25 citation statements)
references
References 51 publications
(29 reference statements)
1
24
0
Order By: Relevance
“…Similarly, our results show that postprandial plasma insulin concentration is higher and ghrelin lower after a breakfast containing GMP compared with an AA-based breakfast. Weigel et al [47] found oral AAs given with macronutrients increased insulin concentration to a greater degree and gave a more stable ghrelin concentration than pure AAs in individuals with PKU. Moreover, whey proteins have been shown to be insulinotrophic [48].…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, our results show that postprandial plasma insulin concentration is higher and ghrelin lower after a breakfast containing GMP compared with an AA-based breakfast. Weigel et al [47] found oral AAs given with macronutrients increased insulin concentration to a greater degree and gave a more stable ghrelin concentration than pure AAs in individuals with PKU. Moreover, whey proteins have been shown to be insulinotrophic [48].…”
Section: Discussionmentioning
confidence: 99%
“…Body weight was measured with calibrated devices. Acylcarnitines were analyzed in dried blood spots by tandem mass spectrometry [7] ; AA analysis was carried out as reported previously [8] . Briefly, samples were deproteinized with a 10% sulfosalicylic acid solution.…”
Section: Methodsmentioning
confidence: 99%
“…Our group has previously reported distinctive alterations in the metabolic profiles following ingestion of various dietary amino acid mixtures commonly used in the treatment of PKU [11]. We thus proposed to study bio-element status in children and adolescents with PKU, using highly specific ICP-AES and ICP-MS technologies which provide superior sensitivity (down to part per trillion and/or billion levels in solution, respectively).…”
Section: Introductionmentioning
confidence: 99%